KONSTRUKSI HUKUM PENGATURAN LAPORAN KERJA PERTANGGUNGJAWABAN (LKPJ) KEPALA DAERAH KABUPATEN/KOTA DALAM PERSPEKTIF DESENTRALISASI - Muhammad Tabrani; Achmad Fitrian; Dhoddy A.R Widjajaatmadja (Journal of Innovation Research and Knowledge, 2023)
One of the powers and responsibilities of the regional government in carrying out the wheels of government is regulated in Article 69 paragraph (1) of the 2014 Regional Government Law. The scope of the LKPJ material is the same, even though the Regional Head conveyed the scope of the LKPJ material there are 5 materials. Second, there is no clear standard for providing recommendations by the DPRD regarding the submission of Regional Head LKPj, even though the government has issued Government Regulation Number 3 of 2007 in terms of the body, explanation and attachments of government regulations. The purpose of this study is to analyze the legal construction of the district / city LKPj concept to achieve good regional autonomy. The research method is normative juridical research. The results showed the LKPj concept conveyed by the three Regional Heads (Mayor of Bekasi, Mayor of Tangerang, and Regent of Karawang) in order to realize good regional autonomy, in its implementation it has implemented good regional autonomy according to Van Der Pot, namely material household systems, home systems. stairs formally, and the real household system.